Anticancer Effect of Amygdalin (Vitamin B-17) on Hepatocellular Carcinoma Cell Line (HepG2) in the Presence and Absence of Zinc - El-Desouky, Mohamed A.; Fahmi, Abdelgawad A.; Abdelkader, Ibrahim Y.; Nasraldin, Karima M. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Amygdalin (Vitamin B-17) is a naturally occurring vitamin found in the seeds of the fruits of Prunus Rosacea family including apricot, bitter almond, cherry, and peach. Objective: The purpose of this study was to examine the effect of amygdalin with and without zinc on hepatocellular carcinoma (HepG2) cell line. Methods: MTT assay was used to evaluate the cytotoxicity of amygdalin without zinc, amygdalin + 20μmol zinc, and amygdalin + 800μmol zinc on HepG2 cell lines. The cell cycle distribution assay was determined by flow cytometry. Apoptosis was confirmed by Annexin V-FITC/PI staining assay. Moreover, the pathway of apoptosis was determined by the percentage of change in the mean levels of P53, Bcl2, Bax, cytochrome c, and caspase-3. Results: Amygdalin without zinc showed strong anti-HepG2 activity. Furthermore, HepG2 cell lines treatment with amygdalin + 20μmol zinc and amygdalin + 800μmol zinc showed a highly significant apoptotic effect than the effect of amygdalin without zinc. Amygdalin treatment induced cell cycle arrest at G2/M and increased the levels of P53, Bax, cytochrome c, and caspase-3 significantly, while it decreased the level of anti-apoptotic Bcl2. Conclusion: Amygdalin is a natural anti-cancer agent, which can be used for the treatment of hepatocellular carcinoma. It promotes apoptosis via the intrinsic cell death pathway (the mitochondria-initiated pathway) and cell cycle arrest at G/M. The potency of amygdalin in HepG2 treatment increased significantly by the addition of zinc.
Keywords: zinc